Sovereign Wealth Funds : A Work Agenda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Sovereign Wealth Funds (SWFs) are becoming increasingly important in the international monetary and financial system, attracting growing attention. SWFs are government-owned investment funds, set up for a variety of macroeconomic purposes. They are commonly funded by the transfer of foreign exchange assets that are invested long term, overseas. SWFs are not new, and some of the longer-established funds-for example those of Kuwait, Abu Dhabi, and Singapore-have existed for decades. However, high oil prices, financial globalization, and sustained, large global imbalances have resulted in the rapid accumulation of foreign assets particularly by oil exporters and several Asian countries. As a result, the number and size of SWFs are rising fast and their presence in international capital markets is becoming more prominent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet